IDENTIFIKASI PERBEDAAN ELEMEN DESAIN PADA MOBIL PREMIUM DAN NON-PREMIUM Objek Studi : Mobil Toyota - Muhammad Irfan Nurrachman (Ide dan Dialog Desain Indonesia (Idealog), 2018)
A design product is designed to satisfy the spesific goals of a problem –the functional and aesthethic ones. Along the design process, several elements of design that designer use to satistfy these goals. However, the design is also about meaning. Significance, as a concept in design, explains how forms assume meaning in the ways they are used, or the role and meaning assigned them. Through this paper, it will be shown that the design elements are used to express the premium label that attached to a car. This paper explains about the characteristic of design elements of premium cars and their potential as concept resources for interior design. As the definition of premium car as the upper-range products, this study using cars under brand Toyota that sold in Indonesia. As thereare types of car in several categories, the study can identify the differences of design elements among each type of car in each category. This comparison will identify design elements that differentiate the upper-range car with another in one category. The result of this study shows there are differences in design elements quantity and quality of exploration of design elements attached to premium cars.